ON CONTINUED CULTURE.TRIALS OF LATES CALCARIFER (BLOCH) AND OREOCHROMIS MOSSAMBICUS IN THE PONDS OF KHARLAND RESEARCH STATION, PANVEL, MAHARASHTRA - SINGH, R. K.; SHIRGUR, G. A. (Journal of Indian Fisheries Association, 2015)
Pond culture trials of Lates calcarifer (Bloch) were initiated in. the ponds of Kharland .Research Station, Panvel, from 1985 upto 1989 by adopting varying methods of inputs of commonly available organic substaces comprising deoiled cake of groundnut, rice bran and raw cattle dung. Although provision of zooplanldon generated under phased fertilisation technique resuited in considerable yield level, subsequent trials in combination with direct feed methods gave higher yield. Trials during 1990m91 adopting similar feed input techniques were continued but by stocking the seed of both Lates and Oreochromis m,ossambicus with yield percentage around 72.23 for Lates and 27.73 for Oreochromis. Trials were further continued during next three years. In relation to the organic input levels the yields rate for seven months period was in the range of 119.4 kglha to 250.4 kg/ha for Lates. In case of Oreochromis the yield rate varied between 28.5 to 153.32 kglha indicating the influence of differential stocking rates and size of the seed of two species.